Who knows what about you? Managing topic shifts during 'conversational' social care assessments in England. (November 2022) - Williams, Val; Symonds, Jon
Social care assessments in England are envisaged as conversations, implying an informal and congenial encounter, in which both parties have equal roles. However, a fundamental task during an assessment is to gauge eligibility for resources. This article uses conversation analysis to consider audio recorded data of seven social care assessments in England. The article focuses on topic shifts, where the assessor introduces an 'assessment relevant' topic, and we examine how these shifts are managed. Sometimes assessors used what was said by the client or by the carer as a 'pivot', which could produce a feeling of friendly conversation, but simultaneously lead to an intrusion into the client's personal knowledge domain. Assessors also had other strategies for framing a 'next question', such as noticing something in the environment, referring to previous notes or to previous conversations. The conversation might feel 'friendly', but these tactics could lead to the personal life domain of the client being inadvertently revealed and used as relevant for their assessment.